Scenario Method of Strategic Planning and Forecasting the Development of the Rural Economy in Agricultural Complex - Milyausha T. Lukyanova; Vitaliy A. Kovshov; Zagir A. Galin; Zariya A. Zalilova; Eugene V. Stovba (Scientifica)
The purpose of the study is to justify the use of the universal scenario method of strategic planning and forecasting the development of the agroindustrial complex of the regional rural economy. The scientific novelty of the study lies in the application of a set of theoretical and methodological provisions for scenario planning and forecasting the development of agriculture in the regions, taking into account the assessment of their existing potential and constructing a territorial planning scheme for the priority of participation in the implementation of strategic directions of rural development in agricultural production. The paper presents a territorial model of the priority of participation of the municipal regions of the Republic of Bashkortostan in the implementation of strategic areas in the areas of development of production of grain crops, sugar beet, and oilseeds. The developed scenario method, reflecting the qualitatively heterogeneous directions of the development of enterprises, is formed taking into account the achievement of the strategic goal and potential opportunities of rural areas. This allows determining strategic decisions for the further development of rural areas and integrating them into a uniform industry development strategy. The developed approach is recommended to be used as a guideline in the development of long-term programs for the development of the crop production industry, as well as for adjusting the activities of ongoing programs.